Early tumor shrinkage identifies long-term disease control and survival in patients with lung cancer treated with atezolizumab - Andrew Rowland; Ashley M Hopkins; Ganessan Kichenadasse; Chris S Karapetis; Michael J Sorich (Journal for ImmunoTherapy of Cancer)
Background Preliminary evidence indicates that early tumor shrinkage (ETS) following immune checkpoint inhibitor (ICI) initiation may be associated with survival outcomes in patients with advanced melanoma. ETS has not been explored as a biomarker of survival outcomes or patient-reported outcomes in patients with advanced non-small cell lung cancer (NSCLC) treated with ICIs.Methods The study pooled data from patients with NSCLC in the randomized trials OAK and POPLAR (atezolizumab vs docetaxel; n=1464), and single-arm atezolizumab trials BIRCH and FIR (n=797). The association between ETS (≥10% decrease in pretreatment sum-of-longest diameters of target-lesions at 6 weeks) and overall survival (OS), progression-free survival (PFS), time to deterioration (TDD) in health-related quality-of-life (HRQoL) and physical function (PF) was assessed using Cox proportional hazard analysis.Results ETS occurred in 20% of atezolizumab-treated patients with NSCLC within OAK and POPLAR and was associated with highly favorable OS (HR 0.33, p<0.001), PFS (HR 0.31, p<0.001), TDD in HRQoL (HR 0.73, p=0.01) and PF (HR 0.52, p<0.001). The results were replicated in the BIRCH and FIR data. Atezolizumab-treated patients achieving ETS had markedly improved OS compared with docetaxel-treated patients achieving ETS (24-month OS 55% vs 32%); PFS was also markedly improved (24-month PFS 31% vs 4%). In contrast, for patients not achieving ETS, atezolizumab-treatment was associated with more modest OS (24-month OS 23% vs 20%) and PFS (24-month PFS 3% vs 1%) improvement compared with docetaxel. Overall, the effect size for ETS within the atezolizumab-treated patients was significantly greater than that in the docetaxel-treated patients (P(interaction)=0.002 for OS and P(interaction)<0.001 for PFS).Conclusions ETS is an easily measurable biomarker, predictive of highly favorable survival and patient-reported outcomes with atezolizumab treatment for advanced NSCLC. Further, ETS identifies patients with significantly greater treatment benefit for ICI therapy.